Modelling the Environmental Effects of Railway Vibrations from Different Types of Rolling Stock: A Numerical Study - Georges Kouroussis; David P. Connolly; Konstantinos Vogiatzis; Olivier Verlinden (Shock and Vibration)
This paper analyses the influence of rolling stock dynamics on ground-borne vibration levels. Four vehicle types (Thalys, German ICE, Eurostar, and Belgian freight trains) are investigated using a multibody approach. First, a numerical model is constructed using a flexible track on which the vehicles traverse at constant speed. A two-step approach is used to simulate ground wave propagation which is analysed at various distances from the track. This approach offers a new insight because the train and track are fully coupled. Therefore rail unevenness or other irregularity on the rail/wheel surface can be accurately modelled. Vehicle speed is analysed and the frequency spectrums of track and soil responses are also assessed to investigate different excitation mechanisms, such as carriage periodicities. To efficiently quantify train effects, a new (normalised) metric, defined as the ratio between the peak particle velocity and the nominal axle load, is introduced for a comparison of dynamic excitation. It is concluded that rolling stock dynamics have a significant influence on the free field vibrations at low frequencies, whereas high frequencies are dominated by the presence of track unevenness.